Implementation of Cucumber Juice to Reduce Blood Pressure for Pregnant Women with Hypertension During Pregnancy - Hasanalita, Hasanalita; Satria, Epi; Sanputri, Yen Risa; Rizana, Nia Afnita; Aninora, Novia Rita; Wikarya, Rionitara (Journal of Health Science and Medical Therapy, 2025)
Hypertension occurs in approximately five to ten percent of pregnant women and is a complication that can lead to low birth weight and even death in babies. Cucumbers are known to contain 147 mg of potassium per 100 grams, and are involved in helping lower blood pressure. The study aimed to prove the effectiveness of cucumber juice in reducing blood pressure in pregnant women with hypertension. The study used a Control Group Pretest-Posttest design, with a sample size of 46 pregnant women with hypertension in pregnancy. The results of the statistical analysis showed a significant decrease in systolic blood pressure (p-value = 0.000 (<0.05) and diastolic blood pressure (p-value = 0.003 (<0.05). According to the study findings, cucumber juice administration had a significant effect on lowering blood pressure in pregnant women with hypertension. Therefore, health workers are advised to provide education on the benefits of consuming cucumbers as a natural way to help lower blood pressure in pregnant women with hypertension.